Aplikasi Snack Video dalam Perspektif Hukum Islam - Raudatunnisa Raudatunnisa; Galuh Nashrulloh Kartika MR; Umi Hani (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
One of the most popular applications recently is Snack Video, an application that offers users income by watching videos, checking in, and inviting new friends to use the application. In Islamic law, muamalah does not only follow the pillars and conditions of the contract but the principles of muamalah must also be considered so that the implementation of the contract is valid and in accordance with sharia. If it is categorized in a muamalah contract, getting money from the Snack Video application is like a competition in Islam called ju'alah, in its use this application has not been legally confirmed in accordance with the ju'alah contract. This research will reveal how to earn money through the Snack Video application and how to analyze contracts and muamalah principles in the Snack Video application. The field research conducted online with Snack Video users was selected using a case study approach through sampling methods from various places in the Barito Kuala district. Data was collected by using interviews, observation, and documentation techniques. The results of this study conclude: first, to earn money from the Snack Video application, users are directed to carry out missions to watch videos, check in, and invite friends. From successful missions, the user will be rewarded with coins that can be exchanged for money. Second, analysis of the contract and muamalah principles in the Snack Video application, the mission in the Snack Video application such as competitions in the muamalah contract is called ju'alah which may be used as a means of making money, provided that the mission carried out does not conflict with Islamic law, the principles muamalah and does not cause harm or immorality. The income obtained from watching the Snack Video application becomes makruh and can even become haram if accompanied by activities that can reduce the value of maqashid sharia on the daruriyyat element, namely hifdz al-mal, protecting property from vanity elements Giving appreciation to content video creators is the same as grants.